Marketing estratégico en la Empresa “Comercializadora Buendía” en la ciudad de Babahoyo, de la provincia de Los Ríos periodo 2023. - Silvera Rivera, Hugo Xavier (2024)
The present study is directed with the line of research financial, administrative, tax management, audit and control, marketing and commercialization, it will be carried out with all the officials of the company “Comercializadora Buendía”, which, this work will benefit the area academic and research career in commerce and administration as well as all people who have access to this project. The strategic plan allows a company to be more proactive, it is essential to be relevant and competitive in a market, the objective of this research is to analyze the strategic marketing of the company "COMERCIALIZADORA BUENDIA" in the Babahoyo Canton, Province of Los Ríos, during